Perspective science (1684-1687), by G.W. Leibniz - Rodríguez Hurtado, Ricardo (Anales del Seminario de Historia de la Filosofía, 2025)
In the present paper is published the translation into Spanish of Perspective science (1684-1686), by G.W. Leibniz Between 1679 and 1686, the German thinker writes a series of texts on perspective science. These writings are the following: The construction and use of scales in perspective; The calculation assistances; The basis of perspective; The origin of the rule of the perspective art; The relationship of points toward the spectator plane; Perspective science. The last of them, which is the most formal and argumentatively completed, is the one that is translated here. In Perspective science, Leibniz defines the discipline, presents a methodology and finds out the rule of the science. The perspective science is, according to him, the art of exhibiting on the Tabula the object’s appearance and, on the said science, the geometrical analysis of intersections is central for discovering the universal rule of representation. Before the translation of the text, it may be found an introductory study of the text aiming to make easier for the reader to understand what Leibniz defends in Perspective science.
Keywords: Leibniz; science; perspective; geometry; history of philosophy